Fitz-Hug-Curtis disease and cholelithiasis: literature review and case report - González Santos, Leonardo; Guzmán, Erick I.; Cruz, Iriani; Higareda, David I.; Reyes, Lizette A. (International Journal of Research in Medical Sciences, 2024)
Fitz- Hug-Curtis disease (FHCS) was first documented in 1930 and has subsequently gained increasing recognition as a rare complication of pelvic inflammatory disease (PID) in which microorganisms that cause sexually transmitted infections are commonly implicated. Methods: It is a Case Report of the classic presentation of FHCS that typically involves systemically healthy women in fertile age, who present with acute atypical abdominal pain in the right upper quadrant that is often confused with another hepatobiliary or gastrointestinal pathology. The diagnosis was confirmed by laparoscopy, which allows the classic adhesions reminiscent of the strings of a violin to be visualized and the infectious agent responsible for pelvic disease to be isolated.